2006
DOI: 10.1139/g06-102
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and geographical dispersal in grapevine clones revealed by microsatellite markers

Abstract: Intravarietal genetic diversification associated with geographical dispersal of a vegetatively propagated species was studied using grapevine Vitis vinifera L. 'Cabernet Sauvignon' as a model. Fifty-nine clonal samples obtained from 7 countries (France, Chile, Spain, Australia, Hungary, USA, and Italy) were analyzed using 84 microsatellite markers. Eighteen polymorphic microsatellite loci (21.4%) were detected, finding 22 different genotypes in the population analyzed with a genetic similarity of over 97%. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 35 publications
2
37
2
1
Order By: Relevance
“…According to the results obtained from the dendrogram, all the genotypes were divided into nine separate groups at a similarity index 0.508. The first group contained 24 genotypes, includ- In some studies intraspecies genetic diversification of V. vinifera corresponded to geographical dispersal (Moncada et al 2006). However, in the present study, the dendrogram generated using Jaccard's similarity index showed that the observed genetic diversity of cultivated and wild grape material sampled in Azerbaijan is not geographically structured, like the researches of Maia et al (2009) performed on Italian grape cultivars.…”
Section: Resultscontrasting
confidence: 57%
“…According to the results obtained from the dendrogram, all the genotypes were divided into nine separate groups at a similarity index 0.508. The first group contained 24 genotypes, includ- In some studies intraspecies genetic diversification of V. vinifera corresponded to geographical dispersal (Moncada et al 2006). However, in the present study, the dendrogram generated using Jaccard's similarity index showed that the observed genetic diversity of cultivated and wild grape material sampled in Azerbaijan is not geographically structured, like the researches of Maia et al (2009) performed on Italian grape cultivars.…”
Section: Resultscontrasting
confidence: 57%
“…using the UMC1446, UMC1590 and UMC2343 primers (Rupp et al, 2009). The triallelic pattern in SSR loci has been considered evidence of chimeras, a mechanism of genetic diversification well characterized by Hocquigny et al (2004) occurring in grapevine clones (Crespan, 2004;Moncada et al, 2006). The detection of 3 alleles at the same locus could be the result of a chimeric structure in which genotypes of different cell layers displayed different alleles.…”
Section: Resultsmentioning
confidence: 99%
“…Somatic mutation could have also contributed to shaping diversity (Antolin and Strobeck, 1985;Moncada et al, 2006). An illustration of this phenomenon is the large clonal diversity of grape varieties, relative to their age and diffusion (43 distinct clones of Pinot Noir and 26 of Cabernet-franc certified in France; ENTAV-ITV, 2007).…”
Section: Molecular Evolution Of Grape Colourmentioning
confidence: 99%